The lexical dominant in poetic text - Hakobyan, Levon (Bulletin of Yerevan University H: Russian Philology, 2023)
The article is an attempt of further development of the concept of "dominant" - one of the most important concepts of Russian formalism. A study of the formalists’ works devoted to the dominant shows that they are focused on the study of general theoretical problems of literature from the point of view of the new concept, so they were not interested in studying the dominant in a particular poem. The purpose of this article is to identify the main problems of the dominant in a poetic text and to consider the features of the lexical dominant. The proposed concept is based on the following provisions. The dominant is a poetic image that prevails over other images of the text. Only the accented component of the text can act as a dominant. The main indicator of accentuation is the intensive repetition of some element in a poetic text, so only a repeating component can be a dominant. It is known that a poetic image can be created at any level of text organization, consequently, the dominant in a poem also can be realized at all text levels. From the perspective of the traditional division of repetition into contact and distant ones, we can assert that the repetitions at the levels lower than the lexical one can actually function only in contact realization, whereas the repetitions at the levels higher than the lexical one can function only in distant reproduction. The lexical repetition which can be both contact and distant is between these two extreme levels. The contact repetition performs mainly an expressive function, so its role in the formation of the dominant is insignificant. More important is the distant and especially the throughout repetition, which implies the presence of a separating space between the repeating text components and their implementation in different micro-contexts. The distant repetition as a dominant has a number of features that distinguish it from other repetitions: a) the dominant is a developing image, the initial and the final states of which are not equal to each other; b) the dominant is a generative image which creates a number of accompanying images that contribute to the promotion of the dominant and the expansion of its presence in the text.